Rancang Bangun Engine Health Control System dan Real-Time Monitoring Berbasis IoT untuk Heavy Equipment di PT Dok Pantai Lamongan - Rizal Hidayat, Fatchur; Made Yulistya Negara, I; Setiono, Agus (Journal of Comprehensive Science, 2025)
The shipbuilding industry, especially at PT Dok Pantai Lamongan, relies on the use of heavy equipment in the production process. However, these machines often suffer from mechanical damage that can interfere with operational efficiency. This research aims to design and develop an IoT-based Engine Health Control System and Real-Time Monitoring to effectively monitor the condition of heavy equipment machinery. The research method used is qualitative descriptive with a case study approach. Data were collected through field observations, interviews, literature studies, and secondary data. The results of the study show that the developed system successfully monitors important parameters such as oil pressure, engine temperature, RPM, and battery voltage in real-time. The implementation of this system can reduce engine downtime by 22.58%. This system offers more economical costs than similar commercial tools, but is still flexible to suit the needs of the company. The conclusion of this study is that IoT-based Engine Health Control System and Real-Time Monitoring can improve the operational efficiency and reliability of heavy equipment by identifying potential breakdowns early, thereby optimizing maintenance and reducing long-term maintenance costs.